Anaplasma phagocytophilum in sheep and goats in central and southeastern China - Yang, Jifei (Parasit Vectors, 2016)
BACKGROUND: Anaplasma phagocytophilum is wide spread throughout the world and impacts both human and animal health. Several distinct ecological clusters and ecotypes of the agent have been established on the basis of various genetic loci. However, information on the genetic variability of A. phagocytophilum isolates in China represents a gap in knowledge. The objective of this study was to determine the prevalence and genetic characterization of A. phagocytophilum in small ruminants in central and southeastern China. METHODS: The presence of A. phagocytophilum was determined in 421 blood samples collected from small ruminants by PCR. Positive samples were genetically characterized based on 16S rRNA and groEL genes. Statistical analyses were conducted to identify ecotypes of A. phagocytophilum strains, to assess their host range and zoonotic potential. RESULTS: Out of 421 sampled small ruminants, 106 (25.2%) were positive for A. phagocytophilum. The positive rate was higher in sheep (35.1%, 40/114) than in goats (26.4%, 66/307) (P < 0.05). Sequence analyses revealed that the isolates identified in this study were placed on two separate clades, indicating that two 16S rRNA variants of A. phagocytophilum were circulating in small ruminants in China. However, analysis using obtained groEL sequences in this study formed one cluster, which was separate from other known ecotypes reported in Europe. In addition, a novel Anaplasma sp. was identified and closely related to an isolate previously reported in Hyalomma asiaticum, which clustered independently from all recognized Anaplasma species. CONCLUSIONS: A molecular survey of A. phagocytophilum was conducted in sheep and goats from ten provinces in central and southeastern China. Two 16S rRNA variants and a new ecotype of A. phagocytophilum were identified in small ruminants in China. Moreover, a potential novel Anaplasma species was reported in goats. Our findings provide additional information on the complexity of A. phagocytophilum in terms of genetic diversity in China. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13071-016-1880-z) contains supplementary material, which is available to authorized users.